The great automatic grammatizator and other stories - Dahl, Roald (London, Puffin books, 2013)
Thirteen of Roald Dahl's most unexpected tales. Is it really possible to invent a machine that does the job of a writer? What is it about a landlady's house that makes it so hard for her guests to leave? What does Sir Basil Turton value most, his wife or one of his priceless sculptures?
Keywords: English fiction